2018
DOI: 10.1111/jsap.12854
|View full text |Cite
|
Sign up to set email alerts
|

Intradural extramedullary granular cell tumour in a cat

Abstract: A 7-year-old domestic shorthair cat was evaluated for progressive paraparesis, inability to jump, a paralysed tail and inability to void the bladder. Neurologic examination was consistent with a L4-S3 localisation. Survey radiographs of the lumbar vertebral column revealed L4-L7 vertebral body remodelling. A pre-contrast T1-weighted hyperintense, diffusely enhancing intradural lesion extending from L4 to S1 vertebral bodies was detected by MRI. Large, mesenchymal, round-to-polygonal cells arranged in nests or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…81 In cats, CNS GCTs have been described in the brain and spinal cord. 64,114 Grossly, GCTs are well demarcated, extraparenchymal, and typically attached to the meninges. 36 Histologically, tumors are characterized by nests or sheets of round neoplastic cells with abundant cytoplasm containing periodic acid-Schiff (PAS)-positive, diastase-resistant granules and eccentric nuclei with dense chromatin.…”
Section: Other Neoplasmsmentioning
confidence: 99%
See 2 more Smart Citations
“…81 In cats, CNS GCTs have been described in the brain and spinal cord. 64,114 Grossly, GCTs are well demarcated, extraparenchymal, and typically attached to the meninges. 36 Histologically, tumors are characterized by nests or sheets of round neoplastic cells with abundant cytoplasm containing periodic acid-Schiff (PAS)-positive, diastase-resistant granules and eccentric nuclei with dense chromatin.…”
Section: Other Neoplasmsmentioning
confidence: 99%
“…36 Histologically, tumors are characterized by nests or sheets of round neoplastic cells with abundant cytoplasm containing periodic acid-Schiff (PAS)-positive, diastase-resistant granules and eccentric nuclei with dense chromatin. 64,114 Neoplastic cells exhibit diffuse immunolabeling for vimentin, S-100, neuron-specific enolase, and desmin. 114 Although GCTs were classified as a type of meningioma (granular cell meningioma), 47 electron microscopy studies revealed that neoplastic cells lack desmosomes or gap junctions, ruling out a meningeal origin.…”
Section: Other Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation